Analysis of The Influence of The Unemployment Rate and HDI on Poverty Levels in Province of Central Java - Liliana Handayani (Journal of Economic Education, 2023)
The high level of poverty in Central Java shows that the process of economic development has not been able to increase people's welfare evenly. Thus, an analysis is needed to determine the factors that influence poverty in the context of overcoming poverty. The aim of this research is to analyze the Unemployment Rate, Human Development Index (HDI) on poverty in 35 Regencies/Cities in Central Java Province from 2016 to 2020. This research uses secondary data with cross-section data consisting of 35 Regencies/Cities in the Province Central Java and time-series data, namely 2016-2020. The analytical tool used to estimate the panel data regression model is the Fixed Effect Model (FEM) or also called Least Square Dummy Variable . The results showed that the HDI variable had a negative and significant effect on the poverty level. Meanwhile, the Open Unemployment Rate has a positive and significant effect on the Poverty Level. Based on the research results, the government is advised to coordinate with related agencies in formulating policies to improve the quality of education and optimize health services.